PENGARUH PENERAPAN ETIKA BISNIS TRAVEL UMRAH TERHADAP KEPUASAN JAMAAH UMRAH PADA TRAVEL DI TASIKMALAYA - Samsul Anwar; Hasan Basri; Restu Gustina (Prodi Manajemen Haji dan Umrah Fakultas Syariah UNIK Cipasung, 2024)
This research is motivated by the existence of every consumer who wants satisfaction in laundry services so as not to be disappointed with the results. Like neat, clean, fragrant clothes, not confused with others and the price is in accordance with quality. The application of Islamic business ethics is one of the most important elements of doing business. Because Islamic business ethics is a driver to generate consumer satisfaction. Therefore, companies must be able to implement indicators of Islamic business ethics including justice, responsibility, free will, truth, honesty and ihsan. Without the application of Islamic business ethics, the satisfaction given to consumers will not be in accordance with what is expected. The purpose of this study is to determine the extent of the influence of the application of Islamic business ethics on consumer satisfaction in the home industry of Laundry Houses. To obtain this study, the authors used data collection techniques in the form of questionnaires, interviews and observations. The research approach uses a quantitative approach with research methods based on positivism. For data processing, the author uses the SPSS 22 application. The results of this study show that: (a) There is a positive and significant influence on the variables of Islamic business ethics (X) in the Home Laundry Home Industry. With the results of the respondent's answer is affirmative. This proves that laundry entrepreneurs in managing Islamic business ethics indicators have run well. (b) The application of Islamic business ethics has been well implemented by the Laundry House entrepreneur. (c) The results of the partial test (Test t) have a positive influence on the independent variable of Islamic business ethics on the dependent variable of consumer satisfaction in the home industry of the Laundry House. This can be seen from the value of t calculated > t table with a value of 5.202 > 2.639 at a significant level of 5%. But this shows that Islamic business ethics in the Laundry House has provided justice, responsibility, free will, truth, honesty and respect for consumers according to their needs. This means that the more Islamic business ethics are applied, the more consumer satisfaction will increase.